Incorporating the Developmental Considerations in a Proposed Forgiveness Education Intervention for Suicidal Adolescents - Jiahe Wang Xu; Shih-Tseng Tina Huang; Robert D. Enright (MDPI AG, 2024)
This paper first explores the risk factors associated with adolescents' suicidal thoughts, attempts, and behaviors within different developmental domains and in the environment, using the developmental systems theory (DST). The most frequently identified risk factor for suicide, psychological pain, is examined in terms of its nature, expression, and possible cause. This paper criticizes the current empirical research of suicidal adolescents' interventions on two issues: (1) lack of concern for fundamental issues in lifespan development and (2) inadequate treatment of the emotional needs resulting from the psychological pain in adolescents. Finally, this paper proposes forgiveness education intervention as targeting the emotional needs, particularly psychological pain, for suicidal adolescents.